Needlescopic intragastric surgery facilitated by newly developed 2mm instruments. Issue 4 (3rd July 2016) - Kanehira, Eiji; Tanida, Takashi; Kamei, Aya; Nakagi, Masafumi; Yoshida, Tomohiko; Touma, Sachiko
Abstract: Background: Intragastric surgery is a percutaneous endoluminal surgery in the stomach aimed at resection of tumors located at the esophagogastric junction (EGJ). We developed needlescopic intragastric surgery performed via 2 mm, 2 mm, and 5 mm ports (PEIGS-225). Material and methods: In cooperation with Niti-On Co., Ltd. we developed a series of 2 mm instruments including grasping forceps, a cannula, a laparoscope, an electrocautery, scissors, and a needle holder. Operative technique: Two 2 mm trocars and a 5 mm one are inserted into the gastric lumen percutaneously. Intragastric procedures are performed by the instruments brought through those three ports. The specimen is extracted via the esophageal-oral route. The defect in the gastroesophageal wall is closed by hand-suture. After the intragastric procedure, the 5 mm stab wound on the gastric wall is closed by hand-suture, while the 2 mm wounds are left untreated. Patients : Between March and August 2015 PEIGS-225 was performed in five patients. Results: There was no operative conversion. The mean operation time was 96 minutes. There were no perioperative complications. Pathological findings indicated that the margin was negative in all cases. Conclusion: Needlescopic intragasric surgery performed via the smallest access (2 mm, 2 mm, 5 mm) is enabled by the 2 mm instruments developed by us.